Maternal Hemoglobin and Its Relationship With fetal birth weight - Momina Asaf, Muhammad Khurram Ilyas, Tooba Qasim, Amer Shoaib, Shazia Irfan, Aijaz Zeeshan Khan Chachar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The needs of iron for mother and fetus considerably increase during pregnancy. Its deficiency can be harmful to the mother’s health and the fetal in terms of birth weight. Aim: To examine the relationship between hemoglobin level and fetal birth weight. Methods: This was an observational study, conducted in Govt. Hospital Samanabad, Lahore between April 2021 and April 2022. A total of 106 pregnant women through non probability convenience sampling were recruited in our study. The patients were divided into two groups according to low and normal hemoglobin level. The hemoglobin<11 g/dl was considered low and the hemoglobin ≥11 g/dl was considered normal. Variables like age, Gravida, gestational age at the time of deliveryand fetal birth weight were recorded. The hemoglobin during first trimester of pregnancy was also recorded from medical records of patients. Results: The prevalence of low hemoglobin in our study population was73.6%. The mean age of the women was 25.09±4.74years. The average gestational age at the time of delivery was 271.15±5.61 days. The participants with primigravida were in majority 54.7% as compared to the multigravida 45.3%. Pregnant females with the low Hb level were more likely to have a baby with the birth weight of less than 2500 grams. Hence there was a strong association between birth weight and Hb level (p-value= 0.038). Hemoglobin level was positively correlatedwith the fetal birth weight(r= 0.631, p-value=0.0001). Conclusion: Maternal hemoglobin should be paid more attention even from the first trimester of the pregnancy in order to avoidhigher risk oflow birth weight fetal. Keywords: Fetal birth weight, Hemoglobin, Pregnancy, Anemia, Gravida